Pengaruh Irigasi Defisit pada Stadia Pembungaan terhadap Hasil dan Produktivitas Air Tanaman Kedelai Varietas Anjasmoro (Glycine Max [L] Merr Var. Anjasmoro) - Aini, Sarifah; Rosadi, R.A. Bustomi; Novita, Dwi Dian (abe.fp.unila.ac.id, 2022)
The purpose of this research was to find out the influence of deficit irrigation at flowering phase toward yield and water productivity of soybean plants. This research held on October 2018 to January 2019 in Integrated Laboratory of Agricultural Faculty, Lampung University. This research used Completely Randomized Design (RAL) with five treatments and four replications. The treatments are 0-100% of available soil water content (ID1), 0-80% of available soil water content (ID2), 0-60% of available soil water content (ID3), 0-40% of available soil water content (ID4), 0-20% of available soil water content (ID5). The result of the yield showed that deficit irrigation at flowering phase had significant effect to all growth variable, growt, and water productivity. The highest production was achieved by the treatment of ID1 amount 24,3 gram. Optimum water productivity was achieved by the treatment of ID2 amount 0,47 g/l.